AN INTERESTING CASE OF MALIGNANT TRANSFORMATION OF MATURE CYSTIC TERATOMA - Ravindran, Saranya; Vishwanath, Usha (European Scientific Journal, ESJ, 2013)
Mature cystic teratomas are common benign tumors of the ovary. They are bilateral in about 10 % of cases. Carcinoma arising from mature cystic teratomas are quite rare and amounts to 0.17 – 2 %. Malignant transformation is most commonly seen in post-menopausal age group, and these carcinomas are treated with surgical excision and adjuvant chemotherapy. In this study, we present a case of a 70 year old lady with carcinoma arising from mature cystic teratoma. She was evaluated clinically, biochemically and with imaging studies, and was taken up for staging laparotomy, Total abdominal hysterectomy with bilateral salpingo opherectomy. Post operatively chemotherapy was given to her. Hence, this rare type of malignant transformation should be kept in mind when faced with a dermoid cyst, especially in older patients, or in patients with larger than usual cysts.